Effectiveness, safety, and Economic Comparison of Two Inhaled Epoprostentol Products (Flolan and Veletri) in Cardiothoracic Surgery Patients. Issue 10 (October 2018) - Hawn, Jaclyn M.; Wanek, Matthew; Bauer, Seth R.; Ammar, Mahmoud A.; Insler, Steven; Adi, Ahmad; Torbic, Heather
Background: No previous studies exist examining two inhaled epoprosternol formulations (Flolan compared with Veletri) in a homogenous cardiothoracic surgery patient population.Objective: To compare the impact of inhaled Flolan and inhaled Veletri on the effectiveness, safety, or cost in cardiothoracic surgery patients.Materials and Methods: This was a retrospective, noninferiority study comparing inhaled Flolan and inhaled Veletri in cardiothoracic surgery patients. Participants included were ≥18 years old, admitted to the cardiothoracic intensive care unit, and received inhaled Flolan or inhaled Veletri therapy for ≥1 hour.Results: A total of 244 patients were included in the primary outcome analysis (122 patients per group). The primary outcome, change in the partial pressure of arterial oxygen to fraction of inspired oxygen (PaO2 /FiO2 ) ratio 1 hour after administration of inhaled Flolan or inhaled Veletri, did not cross the lower limit of the noninferiority margin (95% CI = −14.8 to 65.4). Significant differences in secondary outcomes included duration of mechanical ventilation (4.4 vs 2.6 days; P < 0.01), number of tracheostomies (24 vs 9; P = 0.01), number of patients initiated on dialysis (25 vs 12; P = 0.02), and cost per median duration of therapy (257 vs 183; P = 0.02) in the inhaled Flolan and inhaled Veletri groups, with the average duration of therapy being 1.6 and 1.3 days, respectively.Conclusions and Relevance: Inhaled Veletri was demonstrated to be non-inferior to inhaled Flolan when comparing change in PaO2 /FiO2 ratio 1 hour post –therapy initiation, and inhaled Veletri was an acceptable alternative to inhaled Flolan in a cardiothoracic surgery patient population.